2008
DOI: 10.1007/s10549-008-0291-z
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and predictors of early recurrence in postmenopausal women with estrogen receptor-positive early breast cancer

Abstract: Previous studies suggest that disease recurrence peaks at around 2 years in patients with early stage breast cancer (EBC), but provide no data regarding recurrence type. This retrospective analysis aimed to identify early recurrence types and risk factors in estrogen receptor-positive (ER?) EBC patients treated with adjuvant tamoxifen following breast cancer surgery. Postmenopausal women diagnosed with ER? EBC from 1995 to 2004 were evaluated. Annual hazard ratios (HR) for recurrence at different sites were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
83
2
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 21 publications
5
83
2
4
Order By: Relevance
“…Several studies have investigated the pattern of recurrence. Although definitions of recurrence varied, and some studies include all breast cancer patients regardless of surgical modality, several suggest a pattern of recurrence after breast cancer with more than one peak [11,12] which could represent a difference in time to recurrence depending on tumor characteristics. We found that median time to DM for patients with ER negative tumors were shorter than for those having ER positive tumors (3.0 years vs. 4.5 years), and that for patients with ER negative tumors the majority of DM events would develop within three years, while the risk of developing DM for patients with ER positive tumor would persist.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the pattern of recurrence. Although definitions of recurrence varied, and some studies include all breast cancer patients regardless of surgical modality, several suggest a pattern of recurrence after breast cancer with more than one peak [11,12] which could represent a difference in time to recurrence depending on tumor characteristics. We found that median time to DM for patients with ER negative tumors were shorter than for those having ER positive tumors (3.0 years vs. 4.5 years), and that for patients with ER negative tumors the majority of DM events would develop within three years, while the risk of developing DM for patients with ER positive tumor would persist.…”
Section: Discussionmentioning
confidence: 99%
“…[12,34] In this study the majority of metastases became manifest within 2.5 years of initial diagnosis, as observed by others. [11,13,35,36] The MCR hosts unique data on clinically evident metastases in follow-up, but the prevalence of metastases in the MCR is slightly underdocumented. Surgically treated and histopathologically confirmed metastases are obtained from pathology reports and are therefore nearly complete.…”
Section: Discussionmentioning
confidence: 99%
“…22,23,25,27,28,30 Differences in the binding of letrozole and anastrozole to the aromatase enzyme (Figure 1), and their corresponding inhibitory activity, may in part underlie the more complete suppression of E 2 levels with letrozole versus anastrozole that has been observed in directly comparative clinical studies such as ALIQUOT (Figure 3). It is plausible that the more complete suppression of E 2 in plasma and tissues by letrozole in turn causes a greater eradication of distant micrometastatic breast cancer deposits, which can develop later into fulminant DM recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published study (N = 3614 PMW with operable, estrogen receptor-positive breast cancer receiving adjuvant tamoxifen), a peak of recurrence was reported at 2 years (4.3% per annum), and DM events were found to be the predominant type of early recurrence event at this peak (3.4% per annum). 30 Retrospective analyses from the ATAC and BIG 1-98 trials also confirmed that DM events constitute the majority of recurrence events at 2 years. 25,28 Prevention of DM recurrence is thus a key factor in improving survival and reducing death from breast cancer.…”
mentioning
confidence: 81%